Polymer‐Modified Micromotors with Biomedical Applications: Promotion of Functionalization. Issue 10 (10th August 2022) - Li, Yanan; Wu, Jie; Oku, Hiroyuki; Ma, Guanghui
Abstract : Owing to their autonomous movement characteristics, micromotors can perform various tasks that traditional drug‐delivery carriers fail to perform. The development of adaptable, highly efficient, functional micromotors has become the primary research goal in biomedical field. Micromotors modified with polymers can exhibit strong propulsion ability and unique performance in a complex biological environment, facilitating their application to various complex environments. Herein, different micromotor designs based on natural and synthetic polymers are discussed and the role of polymers in the structure and performance of micromotors is focused on. Overall, the polymer‐modified micromotors can facilitate new developments, particularly in biomedical applications, such as drug delivery and biological detection. Abstract : Micromotors are emerging as an emerging part of the biomedical field. Owing to their autonomous movement characteristics, micromotors can perform various tasks that traditional drug‐delivery carriers fail to perform. The development of adaptable, highly efficient, functional micromotors has become the primary research goal in biomedical field. Micromotors modified with polymers show strong potential for applications in complex biological environments.